MARKETING MIX DAN RELIGI TERHADAP MINAT MASYARAKAT - Wahab, Sulaiman (JURNAL MANAJEMEN DAN AKUNTANSI, 2013)
Abstract: The research arranged to give information around how far interest or proclivity of customer toward sharia banking, especially BNI Sharia in Malang Branch Office by observe their behavior. There are five factor which to have influence their interest, that is : product, price, place and promotion which called as four Pâs or marketing mix and one other factor, that is religion. Religion factor in this case is sharia and faith of individuals. Furthermore by the research, we have two result. First, that the four Pâs are product, price, place, promotion and religion factor very affect Moslem people interest become customer of sharia banking, especially BNI Sharia Malang Branch Office. Second, that religion is a dominant factor which affect Moslem people interest become customer of BNI sharia banking, especially BNI Sharia Malang Branch Office except other factor (four Pâs). Keywords: proclivity of customer, product, price, place, promotion, religion, sharia, behavior.